Clause Chaining and Discourse Continuity in Turkish Children's Narratives - Ögel-Balaban, Hale; Aksu-Koç, Ayhan (Frontiers in Psychology, 2020)
The present study examines the development of complex sentences with non-finite clause combining with particular focus on clause chaining, in narratives of 40 Turkish-speaking 4- to 11-year-olds and six adults elicited by a wordless picture book. Results show a gradual increase by age in the variety of clauses combined, the length of the complex sentences and their frequency of use. Clause chains formed with converbal clauses are the earliest and most frequent type of clause combinations, already present in 4-year-olds’ complex sentences with 1-non-finite clause. Older children’s and adults’ 2- or 3-non-finite clause complex sentences consist of some combinations of adverbial, complement, relative and converbal clauses. Developmentally, clause chains establish first, aspectual-temporal continuity, then temporal-causal continuity. Sentence-internal and cross-sentence-boundary referential continuities are present early, from age 4 onwards. These findings are discussed in terms of the demands of narrative organization as well as the syntactic and semantic complexity of the clause combination devices in Turkish.